Estratégias de enfrentamento no processo de aconselhamento genético em situações de deficiência intelectual grave ou profunda: um estudo clínico-qualitativo - Carvalho, Ellen Zapparoli Nunes de (2019)
Introduction: Coping strategies are techniques used by individuals to adapt to challenging situations and are traditionally classified as problem-focused, emotion-focused, interpersonal coping strategies, or based on spirituality/religiosity. Parents who have children with intellectual disability (ID) experience ambiguous feelings and the coping strategies used by them will indicate the meaning of their experiences. The characterization and understanding of these coping strategies can be useful in clinical interventions and in the planning of public health policies. Aims: This research investigated the coping strategies used by mothers of patients with severe or profound ID during the genetic counseling process. Methodology: This is a clinical-qualitative study carry out with 15 mothers of patients with severe or profound ID, selected by convenience. Data were collected through semi-structured individual interviews. The reports were recorded, transcribed and investigated by the thematic content analysis technique. The results were examined through a comprehensive and interpretative approach. Results: There was a predominance of problem-focused and interpersonal coping strategies that were combined with emotion-focused and spiritual/religious coping strategies. Mothers’ adaptation varied with the stressful events to which they were exposed to and depended on the different degrees of individual tolerance to adverse situations. The higher frequency of problem-focused and interpersonal coping strategies suggested that mothers assessed the situation as likely to be modified and sought institutional and social support to facilitate adaptation to the child's needs and consequently improved their way of life. In general, the religious/spiritual coping strategies were associated with positive outcomes, facilitating the adjustment to the situation. Conclusions: It is necessary to improve external adverse situations by providing adequate support services, especially health services and specific support to the disabled to promote the development of positive coping strategies. Providing orientation on ID and building a comprehensive network of community services and supports are other important factors in coping.